Reference Ranges of Serum Blood Urea Nitrogen, Creatinine Concentration and Ultrasonographic Measurement of the Kidneys in Term Healthy Newborns in the Neonatal Period - Şebnem Kader; Mehmet Mutlu; Elif Bahat Özdoğan; Yakup Aslan; İlker Eyüpoğlu; Ayşegül Cansu; Mehmet Sarıaydın; Yüksel Ali Yazıcıoğlu (Medical Network, 2017)
Objective: Acute kidney injury is an important problem in neonates. We conducted a cross-sectional prospective study to determine normal serum blood urea nitrogen, creatinine reference ranges and ranges of ultrasonographic measurement of kidneys in healthy term newborns. Study Design: Blood samples were collected from total 357 healthy newborns at birth (n=45), 1st (n=30), 3rd (n=61), 7th (n=34), 10th (n=132), 14th (n=36), and 28th (n=19) days of life. Renal ultrasonographic was performed by the same two radiologists on 81 newborns aged 10 days. Results: Serum blood urea nitrogen and creatinine concentrations have reached to the highest level at the first day of life and have returned to cord level at the third day of life. There were gradually decrease in serum blood urea nitrogen and creatinine levels after the first day of life. There were significant difference in both right and left renal length, width, and volumes in terms of gender and these parameters were statistically higher in boys than girls (p<0.05). Birth weight of the boys (3548±539g) was statistically higher than girls (3307±405 g) (p=0.028). There was a positive correlation between birth weight and right (r=0.38, p=0.000) and left kidney volumes (r=0.44, p=0.000). Conclusion: Our findings showed that measured blood urea nitrogen and creatinine levels changed in accordance with postnatal days and there was a positive correlation between kidney volume and birth weight of newborns. We concluded that these findings are important for evaluation of acute kidney injury and for screening of for urinary tract anomalies in neonates